Optimization of Increasing Learning Motivation and Entrepreneurial Interest for Students at the Al-Imran Orphanage, Gowa Regency - Retyana Wahrini; Supriadi; Hasbi (ENGAGEMENT: Jurnal Pengabdian Masyarakat, 2025)
The process of applying the knowledge learned at the University to help society as a whole is known as community service activities. At the Al Imran Orphanage in Gowa Regency, South Sulawesi, is a place for implementing community service activities that aim to encourage students' interest in entrepreneurship, especially to help the community around the orphanage. In this community service activity, children at the orphanage are taught how to make "Es Fruit Jelly Ball" and are motivated to learn. The results of the community service activities at the Al Imran Orphanage, Gowa Regency have gone smoothly, as evidenced by the active participation of the UNM Faculty of Engineering and the Al-Imran Orphanage, Gowa. Through this community service activity, it is hoped that it can help them in entrepreneurship at the orphanage, as well as strengthen the sense of brotherhood between educational institutions and social institutions.